MENINGKATKAN KREATIVITAS ANAK USIA 5-6 TAHUN MELALUI MEDIA FILM ANIMASI (Penelitian Tindakan di TK Islam Tirtayasa Cipocok Jaya, Serang-Banten) - Yuyun Suarsih (Early Childhood Teacher Education Department UNIVERSITAS SULTAN AGENG TIRTAYASA, 2016)
Basically every child has talent creative without exception, although every child has talent different. Talent creative owned child needs to be improved and fertilized early. Animated film is one of the media learning that can be used to creative children, the stories that contains elements fantasy able to increase and influence imagination students. The aims of this research is knowing of creativity children aged 5-6 years in Kindergarten Islam Tirtayasa Cipocok Jaya, Serang-Banten. The subject of this research werw 11 children ager 5-6 years which concist of 6 girls and 5 boys. The method used in this research is a action research. The cycle consists of planning, action, observation and reflection. This research is a collaboration between researchers with classroom teachers. Data collection teknik enhancing creativity collected through observation guide, field notes, interview guides and documentation. Results of this research were obtained after the authors conducted an observations in two cycles to achieve achievement level standards of child development. The average level of achievement of creativityin children ager 5-6 years in kindergarten Islam Tirtayasa Cipocok Jaya, Serang-Banten, who earlier in pre research at only 33%, in the first cycle with the implementation of as many as 8 eeting reaches 48% and the second cycles by as much as 3 meeting execution reached 84%. Base on the results of the data that has been obtained, it can be concluded that by using the media the animated film in the learning activities, the creativity of children aged 5-6 years increased very well in second semester, academic years 2015-2016 in kindergarten Islam Tirtayasa Cipocok Jaya, Serang-Banten.